STRATEGI MEMPERTAHANKAN KEUTUHAN KELUARGA SOPIR TRUK BERBASIS MODAL SOSIAL DI SURAKARTA - Debby Angga Kumara; Sri Hilmi Pujihartati (Journal of Development and Social Change, 2020)
The objective of research was to find out the strategy taken by truck driver family to maintain its family intactness and to find out the factors that can result in family intactness among truck drivers. This research employed Robert D. Putnam and Michael Woolcock’s Social Capital. This qualitative research with phenomenological approach was conducted in Surakarta. The sampling technique employed was purposive sampling one. The informant of research consisted of 4 families including 4 truck drivers, 4 drivers’ wives, 3 drivers’ children, and 1 member of surrounding society. Data was collected through observation, interview, and documentation. To validate the data, source triangulation was used.  Technique of analyzing data used was an interactive model of analysis from Miles and Huberman. The result of research showed that the strategy of maintaining the intactness of truck driver’s family was taken by all family members including fathers, mothers, and children. The strategy of maintaining family intactness using Putnam’s social capital was understandable. Trust could be seen from openness, honesty, and trust concerning family’s income or expense and many problems. Network could be seen from low education, work system with company, inherited truck driving skill, no talent and competency in other type of job. Norm could be seen from appreciating each other’s right and obligation and livelihood for family members. Meanwhile, the strategy of maintaining family intactness using Woolcock’s social capital was understandable including bonding as indicated with honesty, openness, trust, and smooth communication, intensity of meeting time between truck drivers and families, and individual families’ way of solving problems. Bridging could be seen from individual families with rule/norm developed, obeyed, and implemented to organize their families. Linking could be seen from the work system with distributor company, between truck drivers with their own truck and those working with distributor company using either provision or wholesale system.